Big Data Analytics for Zakat Administration: A Proposed Method (UIN Sunan Kudus, 2021)
Big data analytics have altered the corporate landscape in the last several years, presenting firms with both opportunities and obstacles. On one side, employing big data ability to enhance creating, growing, and encouraging deeper consumer connection, which has become a crucial field of business and study. On the other side, the zakat institution is also accountable for zakat collecting activities and is obligated to consistently improve them. Understanding the strategic relevance of data and the actions that may be taken because of data analysis is vital for zakat institutions. Thus, this study objectives are to provide different data kinds to suit the requirements of big data analytics. The research employed an exploratory approach, which comprised secondary research approaches, which required compiling data from previously published primary research. Several sources of information were employed to create this research, including web research and book reviews. As a result, this research proposes four sorts of data namely identification data, quantitative data, descriptive data, and qualitative data, as a preliminary concept of muzakki data requirements for big data analytics with the purpose of enhancing zakat collection by zakat organizations